Weakly perturbed operator equations in Banach spaces - Zhuravlev, V. F. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We obtain the conditions of bifurcation of the solutions of weakly perturbed operator equations in Banach spaces from thepoint $ε = 0$ and propose a convergent iterative procedure for finding the solutions in the form of parts of the series inpowers of $ε$ with pole at the point $ε = 0$.